Plieth-Kalinowska, Izabela & Adam Musielewicz. 2019. Acceptance and social adaptation of children with developmental dysfunctions, Bydgoszcz: University of Kazimierz Wielki - Rajter, Beata (Society Register, 2022)
This is a review of a book entitled Acceptance and social adaptation of children with developmental dysfunctions, written by Izabela Plieth-Kalinowska and Adam Musielewicz. The monograph shows the specificity and ways of organising the developmental conditions of a child with a disability functioning in different social environments. The publication contains characteristics of theoretical conditions of disability and practical ways of its diagnosis and examples of supporting activities.